RANCANG BANGUN APLIKASI RENTAL PERANGKAT ELEKTRONIK BERBASIS MERN - Michael Ariestian Ariestian; Sasa Ani Arnomo (Computer Based Information System Journal, 2025)
The rapid increase in the demand for flexible and economical access to electronic devices has made electronic device rental services an increasingly popular solution. However, these services still face various challenges, such as limited access to information, manual rental processes, and inefficient payment systems. This study aims to design and develop an electronic device rental application based on the MERN stack (MongoDB, Express.js, React.js, Node.js) integrated with a payment gateway to enhance operational efficiency and user experience. The software development method used is Scrum, which enables rapid iteration through a series of sprints, from user interface design to implementing core features such as inventory management, online booking, and integrated online payments. The development results demonstrate that the application can provide a more structured system for device management, information transparency, and fast and secure transactions. This study contributes an innovative web-based rental system and serves as a reference for the development of similar applications in the future. With its offered features, this application is expected to improve access to electronic devices, support societal needs, and foster the growth of the electronic device rental industry in Indonesia..